Association of Shear Stress with Subsequent Lumen Remodeling in Hemodialysis Arteriovenous Fistulas. Issue 1 (January 2023) - He, Yong; Shiu, Yan-Ting; Imrey, Peter B.; Radeva, Milena K.; Beck, Gerald J.; Gassman, Jennifer J.; Northrup, Hannah M.; Roy-Chaudhury, Prabir; Berceli, Scott A.; Cheung, Alfred K.
Visual Abstract: Abstract : Background: Blood flow-induced wall shear stress is a strong local regulator of vascular remodeling, but its effects on arteriovenous fistula (AVF) remodeling are unclear. Methods: In this prospective cohort study, we used computational fluid dynamics simulations and statistical mixed-effects modeling to investigate the associations between wall shear stress and AVF remodeling in 120 participants undergoing AVF creation surgery. Postoperative magnetic resonance imaging data at 1 day, 6 weeks, and 6 months were used to derive current wall shear stress by computational fluid dynamic simulations and to quantify subsequent changes in AVF lumen cross-sectional area at 1-mm intervals along the proximal artery and AVF vein. Results: Combining artery and vein data, prior mean wall shear stress was significantly associated with lumen area expansion. Mean wall shear stress at day 1 was significantly associated with change in lumen area from day 1 to week 6 (11% larger area per interquartile range [IQR] higher mean wall shear stress, 95% confidence interval [95% CI], 5% to 18%; n =101), and mean wall shear stress at 6 weeks was significantly associated with change in lumen area from 6 weeks to month 6 (14% larger area per IQR higher, 95% CI, 3% to 28%; n =52). The association of mean wall shear stress at day 1 with lumen area expansion from day 1 to week 6 differed significantly by diabetes ( P =0.009): 27% (95% CI, 17% to 37%) larger area per IQR higher mean wall shear stress without diabetes and 9% (95% CI, −1% to 19%) with diabetes. Oscillatory shear index at day 1 was significantly associated with change in lumen area from day 1 to week 6 (5% smaller area per IQR higher oscillatory shear index, 95% CI, 3% to 7%), and oscillatory shear index at 6 weeks was significantly associated with change in lumen from 6 weeks to month 6 (7% smaller area per IQR higher oscillatory shear index, 95% CI, 2% to 11%). Wall shear stress spatial gradient was not significantly associated with subsequent remodeling. In a joint model, wall shear stress and oscillatory shear index statistically significantly interacted in their associations with lumen area expansion in a complex nonlinear fashion. Conclusions: Higher wall shear stress and lower oscillatory shear index were associated with greater lumen expansion after AVF creation surgery.